Empowering students’ minds through a cognitive load theory-based lecture model: A metacognitive approach - Siti Nurma Hanim, Hadie; Asma, Hassan; Mohd Ismail, Z. I.; Hairul Nizam, Ismail; Saiful Bahri, Talip; Ahmad Fuad, Abdul Rahim (Routledge, 2016)
Lecturing is widely considered to be a passive, teacher-centred teaching method that fails to foster learning, yet it remains the most feasible method of teaching among higher institutions. Some modern lectures, aligned with recommendations from published guidelines on effective lecturing, are less didactic and more interactive than others, but little is known about converting the classical knowledge-transfer process of lecturing to actual learning. We introduce a cognitive load theory-based lecture guideline that adopts various types of empirically proven strategies to manage learners’ mental loads during lectures. We conducted a randomised controlled trial to evaluate its effectiveness by determining the between-group difference in cognitive load level, self-perceived learning, knowledge acquisition and knowledge retention. This study discusses the practical application of the guideline and several examples of the principles.